New microscopic evidences of the autochthony of the ferrallitic pedological mantle in the Misiones province, Argentina - Moretti, Lucas Martin; Morras, Hector (Asociación Argentina de Sedimentología (AAS), 2024)
The Misiones province is characterized by a pedological mantle with Ultisols, Oxisols and Alfisols. This ferrallitic clayey material frequently shows one or more siliceous or ferruginous nodular "stony horizons" close to the saprolitized basalt, which are generally associated with "structured horizons". The autochthonous or allochthonous origin of the materials composing these complex profiles has been controversially discussed. In this work, we present the results of new microscopic analyses of thin sections and of sand and silt fractions from several profiles of this pedological mantle. The results show that the "nodular horizons" are formed in the massive basalts by weathering and segregation of saprolitized fragments, which become progressively rounded, ferruginized and indurated. Concurrently, the groundmass in- between the nodules is enriched in clay and iron oxides, developing blocky peds, which gives rise to the "structured horizons". On the other hand, the vesicular porosity fossilized by chalcedony in the solum of a profile demonstrates the residual origin of the soil parent material, developed by the weathering of a vesicular-amygdaloidal basalt bearing hydrothermal quartz veins. In turn, the morphology and the surface texture of quartz grains from the sand and silt fractions analyzed by optical microscopy and by scanning electron microscopy reveal processes of silica dissolution and precipitation and show no signals of eolian transport. In accordance with previous studies, these microscopic results provide clear evidence that the parent material of soils in the Misiones province and the "stony horizons" usually included in these profiles are the result of in situ weathering of the diverse basaltic flows outcropping in the region.